PERENCANAAN PAJAK UNTUK MENGHEMAT PEMBAYARAN BEBAN PAJAK PENGHASILAN PADA PT. DAYAKINDO KU TOUR DAN TRAVEL DI SAMARINDA - Rahmawati, Desy Eka (EKONOMIA, 2019)
Tax planning is the initial stage in tax savings. Tax planning is generally carried out before the financial statements are submitted for the tax base to be calculated which will be subject to tax rates, tax planning in taxes can be done by entering additional costs from the income that has not been included in the company in accordance with the income tax law, or freeing the income that should be released in the law.The problem in this thesis is â€œAre tax planning based on income tax law No.36 year 2008 can save the tax burden payable in the article income tax 29 on PT. Dayakindo KU Tour and Travel?â€. The purpose of this study is to find out and analyze tax planning based on income tax laws number 36 years 2008 relating to the savings on tax payable in article 29 of corporate income tax on PT. Dayakindo KU Tour and Travel.Basic taxation theory with a focus on Tax Planning, Hypothesisâ€ Tax planning under the income tax law number 36 year 2008 can save payable tax expense in article 29 of corporate income tax on PT. Dayakindo KU Tour and Travel.Based on the results of research conducted on the income statement at PT. Dayakindo KU Tour and Travel found that the concept of taxation according to the company has not been able to make tax savings compared to after tax planning in accordance with the provisions of tax laws and tax planning theory therefore the calculation of the company's income statement will be reported in the corporate taxpayer's income tax, after conducting a tax planning analysis, the author gets a tax rate before and after the tax planning that is Rp 133.132.529 and after tax planning is Rp 130.118.103. Based on the conclusions stated, the hypothesis which states that tax planning saves income tax payments PT. Dayakindo KU Tour and Travel be accepted.